Efektivitas Ekstrak Daun Dewa (Gynura Pseudochina (Lour.) Dc) Terhadap Pertumbuhan Candida Albicans Pada Plat Dasar Gigi Tiruan Resin Akrilik - Erwid Fatchur Rahman (Majalah Ilmiah Sultan Agung, 2010)
Daun dewa is tradional medicine plants, containts flavonoid, saponin alkaloid, tannin and atsiri oil. The aim of this research is to know the effect of daun dewa extract to the growth of candida albicans on acrylic resin denture base.The research used 31 heat cured acrylic resin discuses with 10 mm in diameterÂ  and 2 mm in thickness. The subjects were incubated in 10 ml candida albicans suspension for 24 hours at 37â°C. the subjects were divided into 3 groups . each group consisted of 10 acrilic resin discuses soaked in daun dewa extract with different concentration , 25%, 5%, 10%. The control was soaked in sterile aquades. The duration of soaking was 8 hours at room temperature. The solution 0.,01 ml from serial dilutions 10â»Â³ were planted in sabouraund dextrose Agar Media. They were incubated. Four 48 hours at 37â° and the colonies of candida albicans were counted. The collected data were analyzed by using one way Analysis varian and t-test.The result showed that there was a significant difference of daun dewa extract among 2,5%, 5% and 10% concentrations to the growth of candida albicans (p<0.05). the conclution of this research was that the daun dewa extrac has an effect to reduce the growth of candida albicans on acrylic resin denture base. 10% concentrations of daun dewa extract is the most effective in reducing to the growth of candida albicans.Keyword : daun dewa, candida albicans, acrylic resin denture base